2020
DOI: 10.3390/jcm9061831
|View full text |Cite
|
Sign up to set email alerts
|

The Relevant Hormonal Levels and Diagnostic Features of Polycystic Ovary Syndrome in Adolescents

Abstract: Relevance: The clinical picture of polycystic ovary syndrome (PCOS) is extremely polymorphic, especially in adolescence. At the same time, the diagnostic criteria of PCOS in adolescence are still under discussion, and the hormonal parameters, including anti-Mullerian hormone range and hyperandrogenism, are not determined. The aim of the present study was to characterize the pivotal clinical and hormonal features of PCOS in adolescents and to establish the age-specific thresholds of the most essential hormonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 19 publications
1
31
0
1
Order By: Relevance
“…Without PCOM, the mean value of AMH was the same for PCOS patients and healthy controls; however, there are no clear cut-off values for AMH concentrations as for total and free testosterone, especially in adolescents. 13 All of these factors contribute to the lack of standardization and appropriate cut-offs for the different conditions. 14 Our study showed that women with PCOS had significantly higher AMH levels compared with controls, and this was true even for women who did not have HA or PCOM.…”
Section: Amh Levels and Pcosmentioning
confidence: 99%
“…Without PCOM, the mean value of AMH was the same for PCOS patients and healthy controls; however, there are no clear cut-off values for AMH concentrations as for total and free testosterone, especially in adolescents. 13 All of these factors contribute to the lack of standardization and appropriate cut-offs for the different conditions. 14 Our study showed that women with PCOS had significantly higher AMH levels compared with controls, and this was true even for women who did not have HA or PCOM.…”
Section: Amh Levels and Pcosmentioning
confidence: 99%
“…In this clinical analysis the variation of AMH in each subgroup may also be one of the reasons why it cannot be used as a diagnostic marker of PCOS, AMH was signi cantly affected by different characteristics of PCOS. When there was no PCOM, the mean value of AMH was the same as that of healthy controls with PCOM, however, no clear cutoff values for AMH concentrations just the same as total and free testosterone especially in adolescents [13], which all contribute to the lack of standardization and appropriate cut-offs for the different condition [14].…”
Section: Discussionmentioning
confidence: 90%
“…After preliminary search, a total of 1135 papers were obtained, 513 repeated papers were excluded, 524 papers were removed after reading abstracts, and 91 of them were excluded after further reading the full text. Therefore, this meta‐analysis finally included seven studies, 14, 16–21 and four of them mentioned the diagnosis of TT for PCOS 16–19 . The screening flow diagram is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%